2022
DOI: 10.3390/genes13101865
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chinese Herbal Formula on Bone Characteristics of Cobb Broiler Chickens

Abstract: To evaluate the prevention and treatment effect of a Chinese herbal formula (CHF) on the bone disease of Cobb broiler chickens, compare its efficacy with Bisphosphonates (BPs), and provide a theoretical basis for studying the nutritional regulation technology of CHF to improve the bone characteristics of broiler chickens. In this study, 560 one-day-old Cobb broiler chickens were examined for the influence of Chinese herbal formula (CHF) and Bisphosphonates (BPs). Different doses of CHF and BPs were added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…To our knowledge, there is no research examining the effect of MP or mushroom products on the biomechanical properties of bone. Partially in accordance with the current results, previous authors have described that including aromatic plants or essential oils, which are rich in calcium and bioactive substances, in animals’ diets could enhance the structural properties of the bone by improving the absorption of minerals (Zhou et al, 2009 ; Kwiecien et al, 2014 ; Olgun, 2016 ; Rehman et al, 2018 ; Gül et al, 2022 ; Liu et al, 2022 ). Further studies on animals are needed to investigate the potential effect of mushrooms on bone biomechanical properties; in addition, the compounds responsible for this potential effect need to be identified.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, there is no research examining the effect of MP or mushroom products on the biomechanical properties of bone. Partially in accordance with the current results, previous authors have described that including aromatic plants or essential oils, which are rich in calcium and bioactive substances, in animals’ diets could enhance the structural properties of the bone by improving the absorption of minerals (Zhou et al, 2009 ; Kwiecien et al, 2014 ; Olgun, 2016 ; Rehman et al, 2018 ; Gül et al, 2022 ; Liu et al, 2022 ). Further studies on animals are needed to investigate the potential effect of mushrooms on bone biomechanical properties; in addition, the compounds responsible for this potential effect need to be identified.…”
Section: Discussionsupporting
confidence: 91%
“…Although single herbs have made good progress in broiler farming, the advantages of mixed herbs are still noteworthy. As far as we can see, mixed herbs have the potential to modulate broiler growth performance and improve the skeletal characteristics of broilers [ 43 ]. Lipiński et al [ 35 ] reported that the addition of mixed herbs to broiler diets improved the growth performance, carcass traits, and meat quality.…”
Section: Discussionmentioning
confidence: 99%
“… Sun et al (2020) found that Ching'e Decoction, consisting of Eucommia ulmoides, Psoralea corylifolia L, Semen Juglandis , and Allium sativum L, slowed bone loss, improved bone quality, and increased maximum stress and maximum load on the tibia. Liu et al (2022d) showed that Chinese herbal formula could improve the bone characteristics of broilers, including the improvement of bone microstructure and the enhancement of bone strength. The results of this study were similar to those studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous study, the basic formula of Chinese herbal medicine has the effect of improving bone characteristics in broilers ( Liu et al, 2022d ). It was composed of Angelica sinensis, Lycium barbarum, Chinese yam, Salvia miltiorrhiza, Schisandra chinensis, Rhizoma corydalis, Fructus cnidii , and Oyster (5:5:5:1:5:1.6:2:2.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation